The potential role of vitamin C in empowering cancer immunotherapy - Takwa Bedhiafi (14153460) (2022)
Vitamin C also known as L-ascorbic acid is a nutrient naturally occurring in many fruits and vegetables and widely known for its potent antioxidant activity. Several studies have highlighted the importance of using high dose vitamin C as an adjuvant anti-cancer therapy. Interestingly, it has been shown that vitamin C is able to modulate the anti-cancer immune response and to help to overcome the resistance to immune checkpoints blockade (ICB) drugs such as cytotoxic T-lymphocyte antigen 4 (CLTA-4) and programmed cell death ligand 1 (PD-L1/PD-1) inhibitors. Indeed, it was reported that vitamin C regulates several mechanisms developed by cancer cells to escape T cells immune response and resist ICB. Understanding the role of vitamin C in the anti-tumor immune response will pave the way to the development of novel combination therapies that would enhance the response of cancer patients to ICB immunotherapy. In this review, we discuss the effect of vitamin C on the immune system and its potential role in empowering cancer immunotherapy through its pro-oxidant potential, its ability to modulate epigenetic factors and its capacity to regulate the expression of different cytokines involved in the immune response. Other Information Published in: Biomedicine & Pharmacotherapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.biopha.2021.112553 Additional institutions affiliated with: Academic Health – HMC, Qatar University HEALTH